High-hardness antistatic polyurethane elastomer as well as preparation method and application thereof
The development of a high-hardness anti-static polyurethane elastomer with carbon nanotubes and plasticizers addresses the challenge of combining permanent anti-static and high hardness, achieving effective anti-static and durable performance in roller applications.
Patent Information
- Application Number
- CN202411966862.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
Current anti-static roller materials face challenges in achieving both high hardness and permanent anti-static properties, as existing solutions either lose anti-static effectiveness over time or compromise on hardness due to the addition of conductive materials.
A high-hardness anti-static polyurethane elastomer is developed, incorporating specific amounts of carbon nanotubes, plasticizers, and solidifying agents to achieve low surface resistivity and improved durability, with the carbon nanotubes forming conductive pathways and the plasticizers ensuring uniform mixing and increased hardness.
The solution provides a polyurethane elastomer with permanent anti-static properties and high hardness, suitable for use in anti-static rollers, maintaining low surface resistivity and enhancing durability and stretch performance.
Smart Images

Figure BDA0005218562650000071 
Figure BDA0005218562650000081 
Figure BDA0005218562650000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antistatic materials, and more specifically to a high-hardness and antistatic polyurethane elastomer and a preparation method and application thereof. Background Art
[0002] The production methods of polyurethane are divided into the following categories according to the processing technology: mixed polyurethane (MPU), cast polyurethane (CPU), and thermoplastic polyurethane (TPU). Compared with the other two types, CPU has a wider range of raw material choices, a wider range of product hardness, and is particularly suitable for the production of large and medium-sized products. It makes up for the limitations and shortcomings of the processing technology of TPU and MPU products and maximizes the performance advantages of polyurethane elastomers.
[0003] As a conveying part, the wheel surface of the roller needs to directly contact the product, and sometimes it will be subjected to heavy pressure and impact. Therefore, the rubber-coated roller is commonly used at present, which is usually a three-layer structure: the outside is a polyurethane rubber layer, the middle is a connecting layer (connecting the rubber layer and the metal roller core layer to ensure the bonding strength of the rubber layer and the metal roller core layer during the use of the product), and the inside is a metal roller core layer. Polyurethane is used to coat the outer surface of the wheel core to obtain a rubber-coated roller, which can protect the roller core, reduce the noise during the conveying process, and alleviate the impact between the roller and the material. The characteristics of the rubber-coated roller product are small quantity and many specifications and models of the roller core, but the cost of in-mold injection molding (TPU) and compression molding (MPU) molds will greatly increase the manufacturing cost, so CPU is often used to process polyurethane. As the application of rubber-coated rollers in various fields becomes more and more extensive, there are more requirements for polyurethane rubber-coated rollers. For example, in the 3C industry (combining the three major technology products of computers, communications, and consumer electronics), when rubber-coated rollers are used in the semiconductor industry to transport precision electronic components, the rubber-coated rollers are required to have good conductivity (antistatic properties) to conduct away the static charge accumulated by the friction of the rollers, preventing the static charge from breaking through the electronic components and causing damage.
[0004] The surface resistance of ordinary polyurethane materials is greater than 10 10 Ω, which is an insulating material. Therefore, when using polyurethane to make antistatic rollers, it is generally necessary to add conductive materials to the polyurethane matrix to reduce the surface resistance of the polyurethane, thereby achieving the antistatic effect. The conductive materials added to polyurethane are divided into liquid conductive materials and solid conductive materials. Liquid conductive materials are easier to mix evenly in the polyurethane matrix, but the disadvantage is that they will gradually drain from the polyurethane over time, making the roller antistatic ineffective. In addition, if the surface resistance reaches 10 6 -10 8, a large amount of liquid conductive material needs to be added, which will greatly reduce the hardness of the material. For example, the hardness of the polyurethane prepolymer is 90A, but the hardness of the finished product made by adding a large amount of liquid conductive material drops to 70A, which ultimately results in the finished product not being able to have both excellent antistatic properties and high hardness, limiting its application scenarios. Solid conductive materials can make polyurethane permanently antistatic, but the high-hardness polyurethane matrix itself is relatively viscous, and it is difficult for solids to mix evenly, resulting in poor antistatic effect of the final product, and most of the surface resistance can only reach 10 9 Ω.
[0005] Therefore, it is urgent to develop an antistatic polyurethane material with high hardness (rubber coating hardness ≥ 80A), permanent antistatic property and excellent antistatic performance (low surface resistance), which can be further used to prepare antistatic and high hardness rubber coated rollers. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a high-hardness and antistatic polyurethane elastomer and its preparation method and application. The polyurethane elastomer provided by the present invention not only has a permanent and excellent antistatic effect (the surface resistance can be as low as 3.63*10 6 Ω), while ensuring the high hardness of the product (up to 92A), and also has excellent wear resistance and tensile properties (the tensile strength of the polyurethane elastomer under 56.4-81.4kgf can reach 15.881-25.909MPa, and the maximum force elongation can reach 533.177-799.038%), which can be further used to prepare rubber-coated rollers to solve the problem of excessively high surface resistance of rubber-coated rollers. At the same time, the high-hardness polyurethane elastomer meets the use requirements of rubber-coated rollers.
[0007] A first aspect of the present invention provides a high-hardness and antistatic polyurethane elastomer.
[0008] Specifically, a high-hardness and antistatic polyurethane elastomer comprises the following raw material components:
[0009] 100 parts of polyurethane prepolymer, 0.01-3 parts of carbon nanotubes, 10-40 parts of plasticizer, 10-30 parts of curing agent and 0.5-5 parts of auxiliary agent.
[0010] The present invention uses a specific amount of carbon nanotubes as an antistatic agent. The carbon nanotubes can be conductive by forming a path through stacking and connection. The carbon nanotubes have a significant effect on reducing the surface resistance of polyurethane (only 0.01-3 parts of carbon nanotubes need to be evenly dispersed in 100 parts of polyurethane, and the surface resistance of the polyurethane elastomer can be reduced to 10 6 -10 8Ω, while liquid antistatic agent needs at least 10-20 parts to reach this level), giving the polyurethane elastomer excellent antistatic effect, too little carbon nanotubes, weak conductivity, large resistance value, and too much carbon nanotubes, will cause the hardness of the polyurethane elastomer to drop sharply, and when carbon nanotubes are added to a certain extent, even if more carbon nanotubes are added, the resistance of the polyurethane elastomer is almost unaffected, but the cost will be increased. At the same time, the present invention improves the hardness of the polyurethane elastomer by controlling the specific content ratio of the plasticizer.
[0011] Preferably, the polyurethane elastomer comprises the following raw material components in parts by weight:
[0012] 100 parts of polyurethane prepolymer, 0.1-1 parts of carbon nanotubes, 15-30 parts of plasticizer, 15-25 parts of curing agent and 0.5-2 parts of auxiliary agent.
[0013] Further preferably, the polyurethane elastomer comprises the following raw material components in parts by weight:
[0014] 100 parts of polyurethane, 0.1-0.5 parts of carbon nanotubes, 15-25 parts of plasticizer, 15-20 parts of curing agent and 0.5-1.5 parts of auxiliary agent.
[0015] Plasticizers can reduce the hardness of polyurethane prepolymers during the preparation process (for example, they can reduce the hardness of polyurethane from D65 to A90), which is conducive to the full and uniform mixing of other components in the polyurethane, and then the hardness of the final product is increased under the action of the curing agent. If the plasticizer is insufficient, the hardness of the polyurethane prepolymer cannot be reduced, and the components are difficult to mix evenly.
[0016] Preferably, the plasticizer is dipropylene glycol dibenzoate (Benzoflex 988SG).
[0017] Preferably, the curing agent is 4,4'-methylenebis(2-chloroaniline) (MOCA).
[0018] Preferably, the raw materials for preparing the polyurethane prepolymer include a polyisocyanate compound and a polyol compound, the polyisocyanate compound is at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, and p-phenylene diisocyanate, and / or the polyol compound is a polyester polyol and / or a polyether polyol.
[0019] Preferably, the polyester polyol is at least one of polyethylene adipate glycol ester diol, polycarbonate diol, polycaprolactone polyol, polyethylene adipate glycol-propylene glycol ester diol, and polyethylene adipate ether diol.
[0020] Preferably, the polyether polyol is at least one of polytetramethylene glycol, polyethylene oxide (polyethylene glycol) glycol, polypropylene oxide (polypropylene glycol) glycol, and polypropylene oxide triol.
[0021] Preferably, the auxiliary agent includes at least one of an anti-settling agent, a viscosity reducing agent, an antioxidant, a silane coupling agent, and an anti-hydrolysis agent.
[0022] Anti-settling agents can significantly increase the viscosity of the polyurethane matrix, thereby preventing the polyurethane from settling during storage and construction, ensuring its stability and uniformity. Viscosity reducers can effectively reduce the viscosity of the matrix (PTMEG) and improve its fluidity.
[0023] Preferably, the anti-settling agent is at least one of organic bentonite (Hemmings SD-2), polyamide wax (MONORAL8800), and gas phase dioxide (Chuangying AEROSIL E972).
[0024] Preferably, the viscosity reducing agent is an inorganic viscosity reducing agent and / or an organic viscosity reducing agent.
[0025] Preferably, the inorganic viscosity reducing agent is at least one of sodium tripolyphosphate, sodium hexametaphosphate, water glass and sodium carbonate.
[0026] Preferably, the organic viscosity reducing agent is at least one of polyacrylamide, hydrolyzed polyacrylamide, guar gum, polyethylene oxide, sodium carboxymethyl cellulose, and hydroxyethyl cellulose.
[0027] Preferably, the antioxidant is model 1135 antioxidant (liquid) of Foshan Yuansheng Chemical Co., Ltd. and / or triester phosphite antioxidant (168 antioxidant) of Beijing Sananhua Chemical Products Co., Ltd.
[0028] Preferably, the silane coupling agent is γ-aminopropyltrimethoxysilane (KH-550) produced by Nanjing Shuguang Chemical Group Co., Ltd.
[0029] Preferably, the polyurethane elastomer is black in color.
[0030] The second aspect of the present invention provides a method for preparing a high-hardness and antistatic polyurethane elastomer.
[0031] A method for preparing a high-hardness and antistatic polyurethane elastomer comprises the following steps:
[0032] Firstly, plasticizer, carbon nanotube and auxiliary agent are mixed to obtain antistatic liquid; then the antistatic liquid is added to polyurethane prepolymer, centrifuged to obtain polyurethane matrix, and then curing agent is added, and casting, degassing and vulcanization are carried out in sequence to obtain the polyurethane elastomer.
[0033] Preferably, plasticizers, carbon nanotubes and additives accounting for 50% to 60% of the total amount of plasticizers are first mixed to obtain an antistatic liquid; then the antistatic liquid and the remaining plasticizer are added to the polyurethane prepolymer, centrifuged to obtain a polyurethane matrix, and then a curing agent is added, and the polyurethane elastomer is obtained through casting, degassing and vulcanization in sequence.
[0034] Since cast polyurethane is solid at room temperature, it is usually necessary to preheat the prepolymer before casting to make the system reach a certain fluidity, so the system viscosity is very thick, and the small amount of carbon nanotubes added is easy to form local dispersion or agglomeration in the system, and the system cannot exist for a long time. Therefore, the present invention first uses carbon nanotubes and plasticizers to prepare a high-percentage carbon nanotube conductive liquid, and by fully dispersing the carbon nanotubes in the plasticizer in advance, the fluidity of the conductive liquid is improved, and then the liquid-liquid blending and dispersion with the polyurethane prepolymer are performed again, which can ensure the full dispersion of the carbon nanotubes and ensure the uniform dispersion effect in the high-hardness polyurethane, thereby improving the antistatic effect, and this antistatic effect is permanent.
[0035] The role of the plasticizer is to soften the polyurethane and reduce the hardness of the polyurethane so that the carbon nanotubes can be fully and evenly mixed in the polyurethane. The plasticizer is added twice. The role of the first addition of the plasticizer is: when preparing the antistatic liquid, in order to mix the solid carbon nanotubes in the liquid plasticizer, it is convenient for the subsequent carbon nanotubes to be evenly mixed in the polyurethane. The role of the second addition of the plasticizer is to further soften the polyurethane and reduce the hardness of the polyurethane. After subsequent vulcanization, a high-hardness polyurethane elastomer can be obtained. In addition, because the polyurethane itself is very viscous, it is difficult for the carbon nanotubes to be mixed in the polyurethane after the antistatic liquid is added. In this way, it is difficult to form a path to conduct static electricity away, and the surface resistance is high, about 10 9 Ω, the antistatic performance is insufficient, so the present invention also centrifuges after mixing the polyurethane, the auxiliary agent and the remaining plasticizer. Centrifugation at this time helps to fully mix the antistatic liquid with the polyurethane, so that the carbon nanotubes can be fully dispersed in the polyurethane system, thereby greatly reducing the surface resistance of the final product. If the centrifugation step is missing, the surface resistance of the polyurethane will be greater than 10 9 In addition, there is no need to remove solids after centrifugation, because the carbon nanotubes have been fully mixed in the liquid, and the various materials added subsequently will not have coarse solid particles visible to the naked eye.
[0036] Preferably, the mass fraction of the carbon nanotubes in the antistatic liquid is 1-5%.
[0037] Further preferably, the mass fraction of the carbon nanotubes in the antistatic liquid is 2-3%.
[0038] More preferably, the mass fraction of carbon nanotubes in the antistatic liquid is 2-2.5%.
[0039] Antistatic liquids with different carbon nanotube contents have different viscosities. The antistatic liquid with a mass fraction of 2-2.5% carbon nanotubes has better fluidity, while when the carbon nanotube content is increased to about 3%, a viscous antistatic liquid similar to "rice paste" is obtained, which is difficult to pour during preparation. Therefore, the mass fraction of carbon nanotubes in the antistatic liquid is preferably 2-2.5%.
[0040] Preferably, the polyurethane is pre-baked at 70-90° C. for 10-12 hours before use. The purpose of pre-baking the polyurethane is to reduce the viscosity of the polyurethane and activate its chemical groups.
[0041] Preferably, the mold used for casting is coated with a release agent before use, and then preheated at 90-100° C. for 10-15 minutes.
[0042] Preferably, the release agent is at least one of a silicone oil release agent (good release effect, high temperature resistance), a wax-based release agent (low cost, easy to clean, non-corrosive), a polytetrafluoroethylene (PTFE) release agent (low friction coefficient, good chemical inertness), and a water-based release agent (environmentally friendly, easy to clean).
[0043] Preferably, after mixing the plasticizer accounting for 50%-60% of the total amount of the plasticizer and the carbon nanotubes, the mixture is stirred at 1500 r / min for 10-30 min, and then centrifuged for 0.5-2 min using a centrifuge to obtain the antistatic liquid.
[0044] Preferably, the centrifugal speed is 1000-1400 r / min, and / or the centrifugal time is 50-70 s, and / or the centrifugal vacuum degree is 0.6-0.7 kPa.
[0045] Preferably, before adding the curing agent, the polyurethane matrix and the curing agent are preheated respectively, and then the curing agent is added to the polyurethane matrix, the preheating is to heat the polyurethane matrix and the curing agent by microwave for 20-40s respectively, and / or the power of the microwave heating is 500-800W, and / or the temperature of the microwave heating is 70-90° C. Microwave ovens have high heating efficiency and uniform heating.
[0046] Preferably, the power of the microwave heating is one of 500W, 550W, 600W, 650W, 700W, 750W, and 800W.
[0047] Preferably, the pouring and degassing steps include pouring in a mold pre-placed on a vacuum degassing machine, and degassing after pouring is completed.
[0048] Preferably, the vulcanization includes sequentially performing a first vulcanization and a second vulcanization, the temperature of the first vulcanization is 90-110° C., and / or the time of the first vulcanization is 20-40 min, and / or the temperature of the second vulcanization is 90-110° C., and / or the time of the second vulcanization is 15-25 h;
[0049] or,
[0050] The vulcanization is a primary vulcanization, the temperature of the primary vulcanization is 90-110° C., and / or the time of the primary vulcanization is 18-25 hours.
[0051] Further preferably, the vulcanization includes sequentially performing a first vulcanization and a second vulcanization, and after the first vulcanization is completed, the polyurethane is cured, and then removed from the mold, and then placed in an oven for a second vulcanization to complete the curing. In the method of performing two vulcanizations of the present invention, the first vulcanization initially completes the curing, and no cooling is required in the middle, and then the second vulcanization is performed immediately to completely cure, and finally a polyurethane elastomer product is obtained. The method of performing two vulcanizations separately is helpful for the complete reaction inside the product, and prevents the release agent from evaporating or being destroyed due to too long heating time, and avoids the roller from sticking to the mold and being unable to be removed after the vulcanization is completed.
[0052] The third aspect of the present invention provides an application of a high-hardness and antistatic polyurethane elastomer.
[0053] The invention discloses an application of a high-hardness and antistatic polyurethane elastomer in preparing a lagging material.
[0054] A fourth aspect of the present invention provides a roller.
[0055] A rubber-coated roller comprises a metal roller and a rubber-coated material wrapped around the outer surface of the metal roller, wherein the rubber-coated material is the polyurethane elastomer.
[0056] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0057] The present invention adopts polyurethane prepolymer, carbon nanotubes, plasticizer, curing agent and auxiliary agent in a specific ratio as the main raw materials for preparing high-hardness and antistatic polyurethane elastomer, wherein carbon nanotubes are used as antistatic agent, and the dispersion effect of carbon nanotubes in high-hardness polyurethane is improved by using it in combination with plasticizer, thereby improving the overall antistatic effect of the polyurethane elastomer finished product (the surface resistance can be as low as 3.63*10 6Ω), and this antistatic effect is permanent, and at the same time, the hardness of the final polyurethane elastomer is improved (can reach 91A, and can reach 92A after being placed for two weeks), and it also has excellent wear resistance and tensile properties (the tensile strength under 56.4-81.4kgf can reach 15.881-25.909MPa, and the maximum force elongation can reach 533.177-799.038%); the polyurethane elastomer of the present invention can be further used to prepare the rubber-coated shell of the rubber-coated roller, giving the rubber-coated roller good permanent antistatic and hardness. The prepared rubber-coated roller has no bubble defects and can be well used in the conveying lines of 3C, semiconductors, and electronic products. For example, the rubber-coated roller is used to convey precision electronic components, so as to avoid the accumulation of charge between the conveying line and the roller due to friction during the conveying operation process, and the breakdown of the electrodes, capacitors and other precision components of the electronic products during the charge release process. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a diagram showing the mixing of the plasticizer and the carbon nanotubes after stirring in step (1) of Example 1 of the present invention;
[0059] Figure 2 This is a diagram of the antistatic liquid after centrifugation in step (1) of Example 1 of the present invention;
[0060] Figure 3 This is a finished product picture of the rubber-coated roller obtained in Application Example 1 of the present invention;
[0061] Figure 4 This is a finished picture of the rubber-coated roller with bubbles made in comparative application example 3. DETAILED DESCRIPTION
[0062] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0063] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0064] The raw materials used in the present invention are:
[0065] The carbon nanotubes were OCSIAL brand TUBALL (diameter 1.4-2.2 nm, length 20-30 μm).
[0066] Example 1
[0067] A high-hardness and antistatic polyurethane elastomer comprises the preparation raw materials shown in Table 1.
[0068] The method for preparing the above-mentioned high-hardness and antistatic polyurethane elastomer comprises the following steps:
[0069] (1) Preparation of antistatic liquid: Weigh 988SG plasticizer and carbon nanotubes, mix them and stir them at high speed (1500 r / min) for 20 min (such as Figure 1 Then centrifuge for 1 min (as shown in Figure 2 As shown), an antistatic liquid with a mass fraction of carbon nanotubes of 2% is obtained (a mass fraction of 2% means that there are 0.2 parts of carbon nanotubes in 10 parts of antistatic liquid);
[0070] (2) Preheating the resin: 12 hours in advance, pre-bake 100 parts of LF650D polyurethane (Lanxess) at 80°C for 11 hours;
[0071] (3) Mold preheating: Prepare the mold in advance, apply a release agent (silicone oil release agent), and preheat it in an oven to 80°C about 10 minutes before pouring;
[0072] (4) Measuring formula materials: preheated polyurethane LF650D, 10 parts of antistatic liquid (if the antistatic liquid has been stored for a long time, the antistatic liquid needs to be centrifuged for 30 seconds), 15 parts of 988SG plasticizer, 0.3 parts of antioxidant (Foshan Yuansheng Chemical Co., Ltd. Model 1135 antioxidant, liquid), 0.5 parts of silane coupling agent (γ-aminopropyltrimethoxysilane, KH-550), 0.3 parts of hydrolysis resistance agent (Shanghai Langyi Functional Materials Co., Ltd., HyMax 1010) are mixed, and after mixing, centrifuged at 1200r / min for 60s, and the vacuum degree is maintained at 0.6-0.7KPa during the whole process to obtain a polyurethane matrix with conductive effect;
[0073] (5) Adding MOCA: Heat the polyurethane matrix and 20 parts of MOCA in a microwave oven for 30 seconds, then add MOCA to the polyurethane matrix, and centrifuge for 1 minute to obtain the base material;
[0074] (6) Pouring and degassing: Apply a release agent (silicone oil release agent) to the mold in advance, then place the mold on a vacuum degassing machine, pour the base material, and degas after pouring;
[0075] (7) Primary vulcanization: vulcanize in an oven for 0.5 h at 100 °C to complete the initial curing;
[0076] (8) Secondary vulcanization: Vulcanize in an oven for 20 hours at a temperature of 100°C to fully cure and obtain a finished polyurethane elastomer.
[0077] Example 2-3
[0078] Example 2-3 provides a high-hardness and antistatic polyurethane elastomer, which is different from Example 1 in that different amounts of raw materials are used in the preparation, as shown in Table 1.
[0079] The raw materials and amounts used in preparing the high-hardness and antistatic polyurethane elastomers of Examples 1-3 are shown in Table 1.
[0080] Table 1 Preparation materials and their amounts (parts by weight) of Example 1
[0081]
[0082]
[0083] Comparative Example 1 (Too many carbon nanotubes)
[0084] A polyurethane elastomer, which is different from Example 1 in that the amount of carbon nanotubes is increased to 5 parts.
[0085] Comparative Example 2 (too few carbon nanotubes)
[0086] A polyurethane elastomer, which is different from Example 1 in that the amount of carbon nanotubes is reduced to 0.005 parts.
[0087] Comparative Example 3
[0088] A polyurethane elastomer, which differs from Example 1 in that, during the preparation process, vacuum degassing is not performed in step (6) but subsequent pouring and vulcanization are directly performed.
[0089] Comparative Example 4
[0090] A polyurethane elastomer, which differs from Example 1 in that the carbon nanotubes are replaced by an equal weight portion of a liquid antistatic agent (purchased from Shanchenxi New Material Technology Co., Ltd., model TP-02).
[0091] Comparative Example 5
[0092] A polyurethane elastomer, which differs from Example 1 in that the carbon nanotubes are replaced by an equal weight portion of solid conductive agent graphite.
[0093] Application Example 1
[0094] A method for preparing a rubber-coated roller comprises the following steps:
[0095] (1) Pre-treatment of wheel core rubber coating: Use machine tools to process the wheel core tube. First, sandblast the surface of the wheel core to be rubber coated to increase the surface roughness of the rubber coated surface; clean the surface of the wheel core and apply adhesion promoter on the surface;
[0096] (2) Mold processing: string the wheel cores together, install them into the rubber-coated mold, apply mold release agent on the mold surface, put it into the oven for preheating, the oven temperature is 100℃, and preheating is 10 minutes;
[0097] (3) Preparing the rubber coating material: following steps (1) to (7) of the above embodiment 1, after the primary vulcanization, the mold is removed, the rubber coating roller is removed, and placed in an oven, and the secondary vulcanization is continued according to the method of embodiment 1;
[0098] (5) Grinding: After vulcanization, the rubber coating of the roller will overflow, and the overflowing part of the outer surface of the roller is polished.
[0099] Comparative Application Examples 1-5
[0100] The preparation methods of the rubber-coated rollers of comparative application examples 1-5 are different from those of application example 1 only in that the method of embodiment 1 is replaced by the methods of comparative examples 1-5 respectively.
[0101] Product effect testing
[0102] 1. Hardness and surface resistance
[0103] Hardness: GB / T 531-1999 Rubber pocket hardness tester indentation hardness test method.
[0104] Surface resistance: Use an electrostatic management tester to test the surface resistance of the rubber-coated roller. Use the weight method. Use an electrostatic tester. Turn on the electrostatic tester and adjust it to high resistance measurement; insert two test leads into two weights respectively, place the weights on the surface of the object to be measured, and try to make the lower surface of the weights completely contact the object to be measured; read the resistance value after the tester reading stabilizes.
[0105] The above test results are shown in the following table.
[0106] Table 2 Hardness and surface resistance test results of polyurethane elastomer
[0107]
[0108] From the results in the table above, it can be seen that the polyurethane elastomer prepared in Example 1 of the present invention is used for roller coating, and has high hardness and excellent antistatic properties. The surface resistance does not change after being placed for two weeks, indicating that its resistance stability is good. Figure 3 ac shown (where Figure 3 ac are the side view, front view and stereoscopic view of the rubber-coated roller, respectively. The inside is a metal wheel core, and the metal wheel core is wrapped with the black polyurethane elastomer of Example 1. It can be seen that there is no bubble defect on the surface of the rubber-coated roller.
[0109] Compared with Example 1, the amount of carbon nanotubes used in Comparative Example 1 is too much, resulting in a sudden drop in the hardness of the polyurethane elastomer.
[0110] Compared with Example 1, the amount of carbon nanotubes used in Comparative Example 2 is too small, resulting in higher surface resistance and poor antistatic effect.
[0111] Compared with Example 1, in the process of preparing the polyurethane elastomer, Comparative Example 3 did not perform vacuum degassing in step (6) but directly performed subsequent casting and vulcanization. As a result, the internal bubbles of the polyurethane elastomer prepared in Comparative Application Example 3 were not removed, and the gas escaped from the inside during heating, resulting in pores in the rubber-coated roller product ( Figure 4 ab, where the red box marks the air bubble).
[0112] Compared with Example 1, Comparative Example 4 uses a liquid antistatic agent instead, and the surface resistance of the obtained polyurethane elastomer is as high as 10 9 , the antistatic effect is poor.
[0113] Compared with Example 1, in Comparative Example 5, the carbon nanotubes are replaced with graphite, the surface resistance is increased, the graphite is difficult to disperse evenly, and local insulation occurs, resulting in unstable performance of the polyurethane elastomer.
[0114] 2. Wear resistance test
[0115] The test is carried out in accordance with DIN ISO 4649 standard. The test equipment is DIN wear test machine, model DZ-323.
[0116] Test method: First, take the polyurethane elastic prepared in Example 1 as a sample (diameter 16mm, thickness 10mm, wear speed 0.32m / s, sample load 5±0.2N, 80 turns), place the sample (the polyurethane elastomer of Example 1 is made into a cylindrical sample with a diameter of 12-14mm and a height of about 10-15mm) at room temperature for more than 24 hours, then install the sample on the chuck of the wear-resistant machine, lock it with a hexagon socket, and make a mark on the sample, then start the switch, pre-grind the sample for one week, and finally weigh its mass on the electronic balance (recorded as △M1). Prepare 6 identical samples in parallel and conduct parallel tests. The test results are shown in the following table.
[0117] Formal test: clean the debris on the sandpaper, reinstall the sample, start the switch for testing, and record the mass after wear (recorded as △M2) after the test.
[0118] Calculate the wear weight: △M=△M1-△M2.
[0119] The test conditions were all 27.3°C and the humidity was all 65.7% RH.
[0120] Table 3 Wear resistance test results of polyurethane elastomer of Example 1
[0121]
[0122] From the results in the above table, it can be seen that the wear weight of the polyurethane elastomer of Example 1 is 0.075-0.081 g, indicating that the polyurethane elastomer has excellent wear resistance.
[0123] 3. Tensile properties
[0124] The test is carried out using a tension / compression testing machine. The specific test method is as follows:
[0125] (1) Use a clamp to fix the polyurethane elastomer spline (cylindrical spline), one side of the spline is clamped on the test machine table, and the other side is clamped on the upper / lower displacement component of the test machine;
[0126] (2) Setting the parameters of the testing machine so that the upper / lower displacement components move upward uniformly (speed 2 mm / min), the testing machine continuously records the changes in the tensile force and the tensile position during the pulling process;
[0127] (3) When the polyurethane elastomer strip is broken, record the tensile force and the distance the displacement component moves (i.e., the deformation of the strip), and calculate the tensile length by dividing the tensile force by the end surface area of the strip.
[0128] The test results are shown in the following table.
[0129] Table 4 Test results of tensile properties of polyurethane elastomers of Example 1
[0130]
[0131] It can be seen from the above table that the tensile strength of the polyurethane elastomer of Example 1 can reach 15.881-25.909 MPa at 56.4-81.4 kgf, and the maximum elongation can reach 533.177-799.038%, indicating that the polyurethane elastomer has excellent tensile properties.
[0132] The polyurethane elastomers prepared in Examples 2-3 have comparable hardness, antistatic properties, wear resistance and tensile properties to those prepared in Example 1.
Claims
1. A polyurethane elastomer, characterized in that: According to weight parts, it includes the following raw material components: 100 parts of polyurethane prepolymer, 0.01-3 parts of carbon nanotubes, 10-40 parts of plasticizer, 10-30 parts of curing agent and 0.5-5 parts of auxiliary agent.
2. The polyurethane elastomer according to claim 1, characterized in that The polyurethane elastomer comprises the following raw material components in parts by weight: 100 parts of polyurethane prepolymer, 0.1-1 parts of carbon nanotubes, 15-30 parts of plasticizer, 15-25 parts of curing agent and 0.5-2 parts of auxiliary agent.
3. The polyurethane elastomer according to claim 1, characterized in that The plasticizer is dipropylene glycol dibenzoate.
4. The polyurethane elastomer according to claim 1, characterized in that The curing agent is 4,4'-methylenebis(2-chloroaniline).
5. The polyurethane elastomer according to claim 1, characterized in that The raw materials for preparing the polyurethane prepolymer include polyisocyanate compounds and polyol compounds, the polyisocyanate compound is at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, and p-phenylene diisocyanate, and / or the polyol compound is polyester polyol and / or polyether polyol.
6. The method for preparing a polyurethane elastomer according to any one of claims 1 to 5, characterized in that: The steps include: Firstly, plasticizer, carbon nanotube and auxiliary agent are mixed to obtain antistatic liquid; then the antistatic liquid is added to polyurethane prepolymer, centrifuged to obtain polyurethane matrix, and then curing agent is added, and casting, degassing and vulcanization are carried out in sequence to obtain the polyurethane elastomer.
7. The method for preparing a polyurethane elastomer according to claim 6, characterized in that: The centrifugal speed is 1000-1400 r / min, and / or the centrifugal time is 50-70 s, and / or the centrifugal vacuum degree is 0.6-0.7 kPa.
8. The method for preparing a polyurethane elastomer according to claim 6, characterized in that: The vulcanization includes sequentially performing a first vulcanization and a second vulcanization, the temperature of the first vulcanization is 90-110° C., and / or the time of the first vulcanization is 20-40 min, and / or the temperature of the second vulcanization is 90-110° C., and / or the time of the second vulcanization is 15-25 h; or, The vulcanization is a primary vulcanization, the temperature of the primary vulcanization is 90-110° C., and / or the time of the primary vulcanization is 18-25 hours.
9. Use of the polyurethane elastomer according to any one of claims 1 to 5 in the preparation of encapsulation materials.
10. A rubber-coated roller, characterized in that: It comprises a metal roller and a rubber coating material wrapped around the outer surface of the metal roller, wherein the rubber coating material is the polyurethane elastomer according to any one of claims 1 to 5.